Analisis Pengembangan Usaha Dalam Upaya Meningkatkan Penjualan Pada Usaha Bun’s Yoghurt (Jurnal Riset Manajemen dan Akuntansi, 2025)
The study was conducted with the aim of finding out the right strategies for efficient business development in order to increase sales at Bun's Yoghurt located in West Bandung Regency. This study was conducted through a more in-depth business analysis of the Bun's Yoghurt business. The business analysis was conducted by analyzing the market, evaluating the business model and analyzing finances. Based on the results of the study conducted on a private business, it was concluded that Bun's Yoghurt has significant market potential, especially for consumers who care about health. However, to achieve product market fit, Bun's Yoghurt needs to develop the business from several aspects, namely business development from the aspect of human resources, sales and distribution aspects, product aspects and financial aspects. This was done to increase sales at Bun's Yoghurt.